Antibody Functional Assays as Measures of Fc Receptor-Mediated Immunity to HIV - New Technologies and their Impact on the HIV Vaccine Field - D. Wines, Bruce; Billings, Hugh; R. Mclean, Milla; J.Kent, Stephen; Mark Hogarth, P. (Current HIV Research, 2017)
Background: There is now intense interest in the role of HIV-specific antibodies and the engagement of FcγR functions in the control and prevention of HIV infection. The analyses of the RV144 vaccine trial, natural progression cohorts, and macaque models all point to a role for Fc-dependent effector functions, such as cytotoxicity (ADCC) or phagocytosis (ADCP), in the control of HIV. However, reliable assays that can be reproducibly used across different laboratories to measure Fcdependent functions, such as antibody dependent cellular cytotoxicity (ADCC) are limited. Method: This brief review highlights the importance of Fc properties for immunity to HIV, particularly via FcγR diversity and function. We discuss assays used to study FcR mediated functions of HIV-specific Ab, including our recently developed novel cell-free ELISA using homo-dimeric FcγR ectodomains to detect functionally relevant viral antigen-specific antibodies. Results: The binding of these dimeric FcγR ectodomains, to closely spaced pairs of IgG Fc, mimics the engagement and cross-linking of Fc receptors by IgG opsonized virions or infected cells as the essential prerequisite to the induction of Ab-dependent effector functions. The dimeric FcγR ELISA reliably correlates with ADCC in patient responses to influenza. The assay is amenable to high throughput and could be standardized across laboratories. Conclusion: We propose the assay has broader implications for the evaluation of the quality of antibody responses in viral infections and for the rapid evaluation of responses in vaccine development campaigns for HIV and other viral infections.
Keywords: IG